2014
DOI: 10.1016/j.vaccine.2014.08.034
|View full text |Cite
|
Sign up to set email alerts
|

PedVacc 002: A phase I/II randomized clinical trial of MVA.HIVA vaccine administered to infants born to human immunodeficiency virus type 1-positive mothers in Nairobi

Abstract: HighlightsMVA.HIVA vaccine was tested for the first time in HIV-1-exposed infants in Africa.PedVacc 002 had 99% retention of infants over 48 weeks of follow-up.MVA.HIVA was safe, but not sufficiently immunogenic.MVA.HVA did not interfere with routine childhood vaccines except for induction of HBV antibodies.MVA is well suited as a vaccine vector for infants under 1 year of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
(75 reference statements)
0
12
1
Order By: Relevance
“…With regard to temporal associations, a total of 19 articles described the time to detection of neutropenia following vaccine administration [ 11 , 12 , 14 , 15 , 19 33 ]. This ranged from detection on the day of vaccine administration (day 0) in one article [ 31 ] to detection 4 weeks post vaccination in 3 articles [ 14 , 22 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to temporal associations, a total of 19 articles described the time to detection of neutropenia following vaccine administration [ 11 , 12 , 14 , 15 , 19 33 ]. This ranged from detection on the day of vaccine administration (day 0) in one article [ 31 ] to detection 4 weeks post vaccination in 3 articles [ 14 , 22 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In subsequent experiments, the route comparison was limited to subcutaneous versus percutaneous routes, since the subcutaneous route is more commonly used in vaccination studies of MVA vectors. As the utility of MVA as a viral vector for the expression of heterologous antigens is expanding [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]78], we also compared the antibody responses and protection conferred by vaccination with two MVA recombinants, one expressing the HSV-2 glycoprotein D, and the other expressing the H5 hemagglutinin of influenza virus rg/A Viet Nam/1203/2004 (H5N1).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its potential use as a smallpox vaccine in immunocompromised individuals, MVA has the capacity to accommodate heterologous DNA, and express encoded proteins, thus serving as a useful viral vector in vaccine development against different types of pathogens. Several recombinant MVA vectors expressing heterologous proteins of different human pathogens are at various phases of clinical development [20,21] Some of the MVA-vectored vaccines in clinical trials include those expressing human immunodeficiency virus antigens [22,23,24], Mycobacterium tuberculosis 85A antigen [25,26,27], malaria antigens [28,29,30], human papilloma virus antigen [31], hepatitis C antigens [32,33], respiratory syncytial virus antigens [34], influenza virus antigens [35,36,37], Epstein-Barr virus antigen [38,39] and more recently, ebola virus antigens [40]. Several other MVA-vectored vaccines have also been evaluated in preclinical studies [41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, in several phase 1 trials, no adverse events have been observed with the current pox vector and protein HIV-1 vaccine candidates, although the number of infants assessed is small. 6,7,9,10 The vaccine candidates carry no risk of HIV-1 infection because they are either protein only or contain only a single viral gene. The potential benefit is substantial, eliminating infant HIV-1 acquisition and achieving a generation free of HIV-1 infection.…”
Section: Potential Benefits and Risks Of Infant Hiv-1 Vaccinesmentioning
confidence: 99%